A new species of the perciform fish genus Symphysanodon (Symphysanodontidae) from the Arabian Sea off the southwestern coast of India - Anderson, Jr., William D.; Bineesh, K. K. (Zootaxa, 2011)
Symphysanodon xanthopterygion, new species, reported herein from 15 specimens collected near Quilon, India, off the Kerala Coast in the southeastern Arabian Sea, becomes the twelfth described species in the genus. The following characters in combination distinguish S. xanthopterygion from its congeners: parapophyses present on first caudal vertebra, total number of gillrakers on first arch 38 to 42, tubed lateral-line scales 54 to 59, sum of lateral-line scales plus total number of gillrakers in individual specimens 94 to 101, head length 33 to 37% SL, head depth 18 to 21% SL, snout length 5 to 6% SL, body depth 24 to 27% SL, lower caudal-fin lobe bright yellow.